Legal Protection for Indonesian Informal Migrant Workers: Substantive and Comparative Justice - Dwi Arie Isdiyanto; Zainal Arifin Hoesein; Ahmed Kheir Osman (Jurnal Pembaharuan Hukum, 2026)
This study analyzes the alignment of legal protection frameworks for informal migrant workers between Indonesia and destination countries and evaluates the effectiveness of government diplomacy and institutional roles in ensuring substantive and comparative justice. This research uses a normative juridical method with a comparative approach through a review of regulatory literature, institutional documents, and academic works. The analysis shows that Indonesia has relatively strong de jure protection; however, its de facto implementation remains weak due to differences in legal systems, inadequate oversight, unprocedural placement practices, and the kafala system. Malaysia and Singapore also exhibit regulatory limitations. Therefore, the protection of informal migrant workers requires harmonization of international law, strengthening of bilateral agreements, and optimization of diplomatic and institutional capacity to achieve sustainable substantive justice.